Le dessin. - Léonard, Pierre (Paris : Musée d'Art moderne de la Ville de Paris, 1977)
Beuys, Joseph ; Chillida, Eduardo ; Christo ; Degottex, Jean ; Dine, Jim ; Gäfgen, Wolfgang ; Garel, Philippe ; Ipoustéguy ; Janssen, Horst ; Krieg, Dieter ; Oldenburg, Claes ; Sandle, Michaël ; Tàpies, Antoni ; Titus-Carmel, Gérard
Le dessin, ARC 2 Musée d'Art moderne de la Ville de Paris, 17 février - 12 avril 1977
boek